Secondary pneumothorax in end-stage lung disease complicated by noninvasive ventilation and a persistent air leak - McCracken, D; Bedawi, E; Hassan, M; Stavroulias, D; Rahman, N (European Respiratory Society, 2019)
Pneumothorax is a well-recognised complication of end-stage COPD, but the management is often complex and may be complicated by other sequelae of advanced respiratory disease including the requirement for NIV http://ow.ly/vkoJ30mB4nZ.